DNA Methylation Silences Exogenous Gene Expression in Transgenic Birch Progeny - Ma, Minghao; Chen, Xiaohui; Yin, Yibo; Fan, Ruixin; Li, Bo; Zhan, Yaguang; Zeng, Fansuo (Frontiers in Plant Science, 2020)
The genetic stability of exogenous genes in the progeny of transgenic trees is extremely important in forest breeding; however, it remains largely unclear. We selected transgenic birch (Betula platyphylla) and its hybrid F1 progeny to investigate the expression stability and silencing mechanism of exogenous genes. We found that the exogenous genes of transgenic birch could be transmitted to their offspring through sexual reproduction. The exogenous genes were segregated during genetic transmission. The hybrid progeny of transgenic birch WT1×TP22 (184) and WT1×TP23 (212) showed higher Bgt expression and greater insect resistance than their parents. However, the hybrid progeny of transgenic birch TP23×TP49 (196) showed much lower Bgt expression, which was only 13.5% of the expression in its parents. To elucidate the mechanism underlying the variation in gene expression between the parents and progeny, we analyzed the methylation rates of Bgt in its promoter and coding regions. The hybrid progeny with normally expressed exogenous genes showed much lower methylation rates (0–29%) than the hybrid progeny with silenced exogenous genes (32.35–45.95%). These results suggest that transgene silencing in the progeny is mainly due to DNA methylation at cytosine residues. We further demonstrated that methylation in the promoter region, rather than in the coding region, leads to gene silencing. We also investigated the relative expression levels of three methyltransferase genes: BpCMT, BpDRM, and BpMET. The transgenic birch line 196 with a silenced Gus gene showed, respectively, 2.54, 9.92, and 4.54 times higher expression levels of BpCMT, BpDRM, and BpMET than its parents. These trends are consistent with and corroborate the high methylation levels of exogenous genes in the transgenic birch line 196. Therefore, our study suggests that DNA methylation in the promoter region leads to silencing of exogenous genes in transgenic progeny of birch.